PENDUGAAN UMUR SIMPAN IKAN TANDIPANG (DUSSUMEIRIA ACUTTA) ASAP CAIR DI KOTA BITUNG - Nova M. Tumanduk; Hetty Ondang; Itje Wewengkang; Fidel Ticoalu; Dyah Ayu Rakhmayeni; Fernando Wowiling (Politeknik Kelautan dan Perikanan Bitung, 2021)
The purpose of this research is to determine the best liquid smoked tandipang fish product and determine the best storage capacity of liquid smoked tandipang fish. Smoking is a combination of drying techniques and the addition of chemical compounds from wood burning to maintain fish durability. Liquid smoking uses liquid smoke as a smoking medium (Utomo et al, 2012). The use of liquid smoke is to provide a specific color effect, taste, and smoky flavor. The method used in this research is experimental by conducting experiments to see a result. The experimental design used was a randomized block design (RBD) using ANOVA. The materials used are tandipang fish, liquid smoke, chemicals for quality testing and the tools used are gas ovens, drying cabinets, laboratory equipment, containers for placing tandipang fish (para-para). Liquid smoke used is liquid smoke produced by CV. Wulung Prima. Based on the research results, it can be concluded that: 1) The best liquid smoke tandipang fish product is produced by immersing liquid smoke with a concentration of 3% for 45 minutes. 2) Shelf life of the best liquid smoked tandipang fish at room temperature based on the peroxide number, namely 7.2 months.Keywords: Best treatment, liquid smoke, shelflifes, smoking, tandipang fish.